Implementasi Modul IPBA_Ecolisa untuk Meningkatkan Keterampilan berpikir logis dan kritis - Nurasyah Dewi Napitupulu; Miftah; I Wayan Darmadi; Muhammad Jarnawi; Rizki Ilmianih (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines the effectiveness of Earth and Space Science modules integrated with eco-pedagogy and science literacy (IPBA-EcoLisa) in improving students’ logical and critical thinking skills. A pre-test–post-test design was employed with 43 prospective physics teacher students. Data were collected using validated instruments measuring logical and critical thinking abilities and analyzed using N-Gain scores. The results indicate a moderate improvement in logical thinking skills (N-Gain = 0.36), particularly in students’ ability to apply patterns and rules to predict Earth and Space Science issues. Critical thinking skills demonstrated a significant improvement (N-Gain = 0.52), with the most notable gains observed in the Basic Support and Basic Clarification indicators. These findings suggest that integrating eco-pedagogy and science literacy within IPBA learning effectively strengthens higher-order thinking skills while fostering environmental awareness. In conclusion, the IPBA-EcoLisa module represents a promising instructional approach for supporting sustainable science education and enhancing essential cognitive competencies in physics education students.